Gaya Kepemimpinan dan Kompensasi Terhadap Loyalitas Karyawan Dengan Motivasi Kerja Sebagai Variabel Moderasi - Shandy, Yosha Anggita; Suji’ah, Uju (Journal of Economics, Business, Accounting and Management, 2025)
This study aims to determine the effect of leadership style and compensation on employee loyalty with work motivation as a moderating variable. The population of this study were all employees of the University of ‘X’ Yogyakarta. The sample size was 85 employee respondents. The sampling technique was probability sampling. The data collection method was questionnaires. Data testing was carried out using validity tests, reliability tests, classical assumption tests, multiple linear regression tests, coefficient of determination tests (adjusted R2), partial significance tests (t-test), simultaneous significance tests (F-test), and moderation tests (Moderated Regression Analysis). The results showed that: 1) Partial significance test: leadership style has a positive and significant effect on employee loyalty; compensation has a positive and significant effect on employee loyalty; work motivation has a positive and significant effect on employee loyalty; leadership style has a positive and significant effect on work motivation; compensation has a positive and significant effect on work motivation; 2). Simultaneous significance test: leadership style and compensation have a positive and significant effect on employee loyalty; leadership style and compensation have a positive and significant effect on work motivation; 3). Moderation test: work motivation does not strengthen leadership style on employee loyalty but acts as a predictor moderation; Work motivation does not strengthen compensation for employee loyalty but acts as a moderating predictor.